Pyridox(am)ine 5′-Phosphate Oxidase Deficiency: Severe Prenatal Presentation with Hypoxic Ischemic Encephalopathy - Alghamdi, Malak; Arold, Stefan T.; Hasan, Hamdi; Bashiri, Fahad (Journal of Pediatric Epilepsy, 2019)
Pyridox(am)ine 5′-phosphate oxidase (PNPO) deficiency is a rare autosomal recessive vitamin-responsive epileptic encephalopathy that manifests with a clinically and electrographically observable antiepileptic response to pyridoxine or pyridoxal 5′-phosphate (P5P). We report a preterm infant who presented with fetal distress and hypoxic ischemic encephalopathy (HIE) as well as seizures that responded to pyridoxine in the first day of life. The patient was diagnosed with PNPO deficiency and homozygosity for a missense-mutation in exon 7 of the PNPO gene, c.673 c > T (Arg225Cys), which disrupts the P5P binding site on PNPO. P5P with folinic acid achieved good control of the seizures. Riboflavin was introduced in the second year of life. The patient continued to have episodes of breakthrough seizures with sickness. P5P therapy resulted in marked seizure cessation but did not improve neurocognitive function in this patient, who had significant global psychomotor delay at the age of 3 years despite early treatment. We conclude from this report and other reports that HIE is a co-occurring condition with some inborn errors of metabolism. Therefore, PNPO deficiency should be investigated and P5P trial should be considered in case of presumed HIE particularly with familial recurrence of epileptic encephalopathy and refractory seizure.
Keywords: pyridox(am)ine-5-phosphate oxidase; neonatal hypoxic ischemic encephalopathy; inborn error of metabolism